Association of Dietary intake of vitamin E with chronic obstructive pulmonary disease events in US adults: A cross-sectional study of NHANES 2013–2018 - Liu, Ziyi; Su, Yingjie; Chen, Qing; Xiao, Lihua; Zhao, Xue; Wang, Feichi; Peng, Zhenyu; Zhang, Hongliang (Frontiers in Nutrition, 2023)
Abstract Several studies have demonstrated that vitamin E intake is negatively associated with the development of several diseases, but the relationship between vitamin E intake and COPD in different groups of people is not clear. The aim was to investigate the relationship between vitamin E intake and COPD in different groups of people. This study used data from NHANES (National Health and Nutrition Examination Survey) from 2013-2018. A final total of 4706 participants were included, univariate versus multivariate logistic regression and restricted cubic spline models adjusted for confounders were used to explore the relationship between vitamin E intake and COPD, and subgroup analyses were conducted to assess whether there are differences in the relationship between vitamin E intake and COPD in different populations or conditions. After adjusting for potential confounders, higher vitamin E intake showed a significant negative association with COPD. (Model 1(unadjusted covariates, OR=0.48;95% CI:0.33-0.70; P<0.001), Model 2(adjusted for age, sex, and race, OR=0.48;95% CI:0.31-0.73; P<0.01), and Model 3(adjusted for all covariates, OR=0.57;95% CI:0.36-0.91; P=0.02)). And a restricted cubic spline curve showed a significant negative correlation between vitamin E intake and COPD (p for nonlinear=0.2036). In the subgroup analysis, we found a negative association between vitamin E intake and COPD in all subgroups as well. After analyzing data based on the NHANES database from 2013-2018, the results showed that vitamin E intake among U.S. adults was well below the recommended levels and that higher vitamin E intake was negatively associated with COPD incidence.